Deciphering The Immune Landscape: A Comprehensive Review Of Human Immune Responses To Malaria - Lie, Jason Gunawan; Firmansyah, Yohanes (Jurnal Ners, 2024)
This comprehensive review examines the complex human immune response to malaria, a significant global health challenge caused by Plasmodium parasites. The innate and adaptive immune systems play pivotal roles in defending against malaria, with mechanisms involving various immune cells like dendritic cells, natural killer cells, eosinophils, basophils, T cells, and B cells. These cells operate in a dynamic interaction, recognizing and responding to the parasite at different stages of its life cycle. Our review methodologically analyzed recent studies and literature on the immune response to malaria, focusing on the roles of different immune cells and the production of cytokines and antibodies. We also explored the epidemiology of malaria, with particular attention to regions like Indonesia, where climate, geography, and socio-economic factors influence transmission dynamics. The findings highlight the innate immune system's crucial role in early pathogen detection and response, particularly through PAMPs recognition by PRRs such as TLRs and scavenger receptors. Additionally, the adaptive immune response's complexity, including anti-sporozoite antibodies and T cell immunity, is emphasized, particularly in recognizing parasite-exported antigens and developing memory responses for long-term immunity. The immune response's intricacy, coupled with the challenges in vaccine and therapy development due to the parasite's complex life cycle and varying epidemiological patterns, underscores the need for continued research and innovation in malaria immunology and public health strategies. This review contributes to a deeper understanding of the immune mechanisms against malaria and the ongoing efforts to control and eradicate this pervasive disease.